Climate change adaptation planning for Global South megacities: the case of Dhaka. Issue 6 (2nd November 2017) - Araos, Malcolm; Ford, James; Berrang-Ford, Lea; Biesbroek, Robbert; Moser, Sarah
ABSTRACT: Megacities in low- and middle-income countries face unique threats from climate change as vulnerable populations and infrastructure are concentrated in high-risk areas. This paper develops a theoretical framework to characterize adaptation readiness in Global South cities and applies the framework to Dhaka, Bangladesh, a city with acute exposure and projected impacts from flooding and extreme heat. To gather case evidence from Dhaka we draw upon interviews with national and municipal government officials and a review of planning documents and peer-reviewed literature. We find: (1) national-level plans propose a number of adaptation strategies, but urban concerns compete with priorities such as protection of coastal assets and agricultural production; (2) municipal plans focus on identifying vulnerability and impacts rather than adaptation strategies; (3) interviewees suggest that lack of coordination among local government (LG) organizations and lack of transparency act as barriers for municipal adaptation planning, with national plans driving policy where LGs have limited human and financial resources; and (4) we found limited evidence that national urban adaptation directives trickle down to municipal government. The framework developed offers a systematic and standardized means to assess and monitor the status of adaptation planning in Global South cities, and identify adaptation constraints and opportunities.